(untitled) (Journal of Environmental Science and Natural Resources, 2019)
Cadmium (Cd) is a heavy metal which is not essential for human body. Cadmium enters into human body mainly through food consumption. Besides industrial wastes, phosphate fertilizers contain Cd which accumulates gradually in agricultural lands. To produce high quantity of food for about 160 million people of Bangladesh, agricultural lands need to be applied huge amount of fertilizes including TSP which add Cd to soils. It has been reported that in rice grains the cadmium concentrations were the highest in Bangladesh and Srilanka where the per capita rice intake is high, from a survey on four continents of 12 countries. The intake of these Cd containing foods may ultimately increase the Cd concentration in human kidneys and livers which might be related to the enhanced kidney patients in Bangladesh. There is lot of toxic effects of excess Cd on humans. The present review illustrates the urgency of further studies of Cd in Bangladesh. J. Environ. Sci. & Natural Resources, 11(1-2): 227-234 2018